DESKRIPSI PERBEDAAN SITOLOGI NON GRANULOMA LIMFADENITIS TUBERKULOSIS PADA PASIEN HIV AIDS : STUDI KASUS - yafanita izzati nurina (Jurnal Ilmu Kesehatan dan Kesehatan, 2020)
ABSTRACT Introduction: HIV AIDS is a disease with CD4 as the main target and frequently accompanied by lymphadenopathy symptoms. Most lymphadenopathy is caused by tuberculosis. The prevalence of limphadenitis in HIV TB is 40-80%. Cytological features of TB lymphadenitis in HIV AIDS and non-HIV have differences and associated with lower CD4 counts.Case: Male, 58 years old with complaints of right and left neck mass since 1 month. It was enlarged since 1 week, not accompanied by pain and injury. Patient also complained fever, night sweats, weight loss, white spots in the mouth. On physical examination, found right neck mass of 7x6 cm and left of 5x4 cm, flat surface elastic solid mass, difficult to move, no tenderness and inflammation. VCT result of three methods was reactive, absolute CD4 cell count 81.8 cells/UL and 6.13 log copies/mL viral load. Cytology result was hypocellular smears containing large necrotic areas with lymphocyte cells, histiocytes, PMN without signs of malignancy, conclusion: TB lymphadenitis. Patients received anti TB category one and ARV 2 weeks after TB treatment. Discussion: Lymphadenopathy symptoms in HIV AIDS from many etiologies are almost same so a cytological examination is needed. In TB lymphadenitis cytology, there are 3 groups of typical features are granuloma, granuloma with necrosis and only necrosis then it was confirmed ZN staining (smear bacilli). In HIV AIDS is more found necrosis without granuloma except CD4>100. This is because T cell function which is important in the formation of epithelioid granuloma is decreased. At an advanced stage with CD4 decreases, there is no epithelioid cell formation but rather foamy macrophage formation.Conclusion: HIV AIDS patient with CD4 81.8 and cervical tuberculosis lymphadenitis has different cytological features with large necrotic areas without granulomas.